The Effect of Femoral Cutting Guide Design Improvements for Patient-Specific Instruments - Kwon, Oh-Ryong (Biomed Res Int, 2015)
Although the application of patient-specific instruments (PSI) for total knee arthroplasty (TKA) increases the cost of the surgical procedure, PSI may reduce operative time and improve implant alignment, which could reduce the number of revision surgeries. We report our experience with TKA using PSI techniques in 120 patients from March to December 2014. PSI for TKA were created from data provided by computed tomography (CT) scans or magnetic resonance imaging (MRI); which imaging technology is more reliable for the PSI technique remains unclear. In the first 20 patients, the accuracy of bone resection and PSI stability were compared between CT and MRI scans with presurgical results as a reference; MRI produced better results. In the second and third groups, each with 50 patients, the results of bone resection and stability were compared in MRI scans with respect to the quality of scanning due to motion artifacts and experienced know-how in PSI design, respectively. The optimized femoral cutting guide design for PSI showed the closest outcomes in bone resection and PSI stability with presurgical data. It is expected that this design could be a reasonable guideline in PSI.